A Case-control Study of Prevalence of Cholelithiasis among Type 2 Diabetic Patients in Kashmir. - Shakeeb Nabi; Zhahid Hassan; Syed Nazima; Hakim Vaqar (Asian Journal of Medical Research, 2019)
Background: Type 2 Diabetes mellitus and gall bladder stones are both common and co-existent diseases in a significant population. Increasing age, female gender, overweight, fair skin , familial history of the disease and type 2 diabetes mellitus is all associated with an increased risk of gallstones. Several studies from around the world reported an increased prevalence of gall bladder stones in patients with diabetes mellitus. Aims and objectives: The aim of this study was to define the frequency of gall bladder stones among diabetics and to evaluate the possible associated risk factors in these patients.Subjects and Methods:A case control study was performed during 2018 at Government Medical College Baramulla. The study involved 161 randomly selected type-2 diabetic patients under regular follow up at the center, and 166 age and sex matched non-diabetic outpatients. Real-time abdominal ultrasound was performed by a  radiologist to examine the abdomen after an overnight fast.Results:About 40% of the diabetic cohort had gall bladder stones as compared to 17.5% of non-diabetic patients. Females were significantly more affected than males. Patients with gall bladder stones were significantly older and had a significantly higher body mass index than those without stones.Conclusion: The prevalence of gallstones in diabetic patients is higher in Kashmir than the rates reported in other parts of the world. Kashmiri diabetic patients with gallstones tend to be older and more obese than those without gallstones. Duration of diabetes mellitus and type of treatment does not seem to influence the frequency of gall bladder stones among Kashmiri diabetics.